Contrasting carbon metabolism in saprotrophic and pathogenic microascalean fungi from Protea trees. (December 2017) - Aylward, Janneke; Wingfield, Brenda D.; Dreyer, Léanne L.; Roets, Francois; Wingfield, Michael J.; Steenkamp, Emma T.
Abstract: Protea -associated Knoxdaviesia species grow on decaying inflorescences, yet are closely related to plant pathogens such as Ceratocystis albifundus . C. albifundus also infects Protea, but occupies a distinct niche. We investigated substrate utilization in two Knoxdaviesia saprotrophs, a generalist and a specialist, and the pathogen C. albifundus by integrating phenome and whole-genome data. On shared substrates, the generalist grew slightly better than its specialist counterpart, alluding to how it has maintained its Protea host range. C. albifundus grew on few substrates and had limited cell wall-degrading enzymes. It did not utilize sucrose, but may prefer soluble oligosaccharides. Nectar monosaccharides are likely important carbon sources for early colonizing Knoxdaviesia species. Once the inflorescence ages, they could switch to degrading cell wall components. C. albifundus likely uses its limited cell wall-degrading arsenal to gain access to plant cells and exploit internal resources. Overall, carbon metabolism and gene content in three related fungi reflected their ecological adaptations. Graphical abstract: Highlights: Saprotrophic Knoxdaviesia species can utilize the simple sugars in nectar. Cellulose and hemicellulose-degrading enzymes are abundant in Knoxdaviesia . Cell wall-degrading enzymes are limited in the pathogen, Ceratocystis albifundus . C. albifundus lacks key enzymes and transporters to utilize exogenous simple sugars. Carbon metabolism and gene content in related fungi reflect their ecologies.